Sebuah MELACAK MAKNA WORLDVIEW: STUDI KOMPARATIF WORLDVIEW BARAT, KRISTEN, DAN ISLAM: Indonesia - Abdul Rohman; Ahmad Ahmad; Amir Reza; Muhammad Ari Firdausi (Sekolah Tinggi Agama Islam Sadra, 2021)
In this article, we will review the keyword Worldview and its meaning, both from the perspective of Western philosophers, Christian theologians, and Islamic scholars. Worldview is a view of life or philosophy of life that is owned by everyone. This article is a literature study where the data are taken from several books related to worldview. The authors apply qualitative methods with a descriptive-analytic approach in this study. The data that has been obtained and analyzed by the author will then be compared with each other. The results of this study are that Western philosophers, Christian theologians, and Islamic scholars have different views regarding the worldview triggered by differences in their epistemological sources. West and Christianity put reason as a source in determining worldview. So that the worldview of the West and Christianity is changing, because each person’s mind is different and can change. This is different from the meaning of worldview in Islam which comes from divine revelation. The Islamic worldview is absolute, because the divine revelations that are revealed are not the product of human reason, but are direct instructions from Allah. While the West and Christianity only discuss what is visible to the five senses.